Tax issues regarding the Latin American Integrated Market: Scope and Proposals - Maruy, Camilo (2015)
In the present round table, tax specialists from Peru, Colombia, Chile and Mexico discuss about the tax reforms carried out and outstanding in their respective countries on the tax treatment of capital gain within the framework of the Latin American integrated Market.